Strategic Innovations in the Governance of ZISWAF by BAZNAS for Advancing Social Welfare - Ayumi Miranda; Sonia Tiffanny Pricellia; Amala Rosheeda; Faiqotul Muthoharoh; Nurlaili Adkhi Rizfa Faiza (Journal of Community Engagement in Economics, 2025)
Innovative management of Zakat, Infak, Sedekah, and Waqf (ZISWAF) plays an important role in improving social welfare. BAZNAS Trenggalek implements an innovation strategy to optimize the collection, management, and distribution of ZISWAF funds effectively and transparently. The methods used in community service and field surveys for aid recipients include living expenses, house renovations, health services, and education programs such as scholarships and school equipment. The main objective of this community service is to analyze the innovation strategy implemented by BAZNAS Trenggalek in managing ZISWAF to improve community welfare. The results show that the innovations implemented include digitalization of ZISWAF services, strengthening collaboration with the private sector and government, and ZISWAF-based economic empowerment programs. Increased transparency and accountability have contributed to increasing public trust in fund management. The impact of this strategy is reflected in the increasing amount of ZISWAF funds collected and the effectiveness of the distribution program, which provides real benefits to the underprivileged. With this innovative strategy, ZISWAF management at BAZNAS Trenggalek becomes more optimal and sustainable in supporting social welfare. In the future, strengthening collaboration and utilizing technology is expected to further increase the effectiveness of ZISWAF management and expand its impact on society.